PENGARUH MARKETING MIX TERHADAP KEPUTUSAN PEMBELIAN PADA KRIPIK SINGKONG RIDHO-SUSI SILO JEMBER - Hamdani, Bagas Yuda; Sumowo, Seno; Hermawan, Haris (Relawan Jurnal Indonesia, 2022)
The development of industrial business in Indonesia is currently growing very rapidly. This can be seen by the number of industries that are competing to win the hearts of consumers, through improving product quality and others. This development also occurred because of market demand which began to soar after the pandemic. In running a business selling products in the form of goods or services, purchasing decisions are things that must really be considered because consumers are the main target in selling a product, one solution is to use the marketing mix or better known as the marketing mix. In the food and beverage sector, there are many kinds. Over time in the city of Jember, many food industry businesses have sprung up, one of which is the food chip industry, namely Ridho-Susi Silo Jember cassava chips. Where Ridho-Susi's cassava chips Silo Jember is one of the food industries that sells crispy snack products, which is currently experiencing a declining sales trend. The purpose of this study was to determine and analyze the product, price, promotion, location had a significant effect on purchasing decisions of cassava chips in Ridho-Susi Silo Jember. The population in this study were Ridho-Susi Silo Jember cassava chips consumers. The sample used was 80 respondents using a purposive sampling technique. The analysis tool uses multiple linear regression. The results showed that product, price, promotion, location had a significant partial and simultaneous effect on purchasing decisions for cassava chips in Ridho-Susi Silo Jember.